2020
DOI: 10.1101/2020.06.11.146357
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A non-enveloped arbovirus released in lysosome-derived extracellular vesicles induces super-infection exclusion

Abstract: 22Recent developments on extracellular-vesicles (EVs) containing multiple virus particles challenge 23 the rigid definition of non-enveloped viruses. However, how non-enveloped viruses hijack cell 24 machinery to promote non-lytic release in EVs, and their functional roles, remain to be clarified. Here 25 we used Bluetongue virus (BTV) as a model of a non-enveloped arthropod-borne virus and observed 26 that the majority of viruses are released in EVs, both in vitro and in the blood of infected animals. 27Based… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…During BTV infection both lytic and non-lytic virion release has been documented. Further, electron microscopy analysis revealed different forms of virion particles, naked virion particles released by cell lysis and non-lytic viruses budding through the plasma membrane [ 19 ]. In addition to individual particle budding, a recent report demonstrated virion particles are released in aggregates within extracellular vesicles (EVs), suggesting a secretory pathway [ 17 ].…”
Section: Btv Egress: Lytic Versus Non-lytic Releasementioning
confidence: 99%
See 1 more Smart Citation
“…During BTV infection both lytic and non-lytic virion release has been documented. Further, electron microscopy analysis revealed different forms of virion particles, naked virion particles released by cell lysis and non-lytic viruses budding through the plasma membrane [ 19 ]. In addition to individual particle budding, a recent report demonstrated virion particles are released in aggregates within extracellular vesicles (EVs), suggesting a secretory pathway [ 17 ].…”
Section: Btv Egress: Lytic Versus Non-lytic Releasementioning
confidence: 99%
“…Recently, we reported that in some cell types, a majority of BTV particles can be released in extracellular vesicles, both in vitro and in vivo [ 19 ]. The release of BTV containing EVs was initially confirmed by electron microscope analysis of EVs purified from infected cells culture’s supernatants and blood from BTV infected cattle.…”
Section: Btv Release In Extracellular Vesiclesmentioning
confidence: 99%